Species distribution, virulence factors, and antifungal susceptibility among Candida parapsilosis complex isolates from clinical specimens at Siriraj Hospital, Thailand, from 2011 to 2015 - Sujiraphong Pharkjaksu (2019)
The Candida parapsilosis complex has been described as the second or third most common yeast species isolated from patients with bloodstream infections worldwide. This complex consists of three species: C. parapsilosis sensu stricto, C. orthopsilosis, and C. metapsilosis. The distribution of species in this complex has never been studied in Thailand. Here we investigated the molecular epidemiology, in vitro on virulence factors, and antifungal susceptibility profiles of isolates of these three species collected from patients in Siriraj Hospital, Thailand, from 2011 to 2015. Of the 96 C. parapsilosis complex isolates analyzed, 66 (68.75%) were identified as C. parapsilosis sensu stricto, 28 (29.17%) as C. orthopsilosis, and two (2.08%) as C. metapsilosis. Most strains were isolated from blood (81.25%). Proteinase activity was only detected in four (6.06%) and two (7.14%) isolates of C. parapsilosis sensu stricto and C. orthopsilosis, respectively. Sixty (90.91%) isolates of C. parapsilosis sensu stricto, 12 (42.86%) isolates of C. orthopsilosis, and all C. metapsilosis isolates showed phospholipase activity. Psuedohyphae formation was only detected in 33 (50%) and 15 (53.57%) isolates of C. parapsilosis sensu stricto and C. orthopsilosis, respectively. All isolates were susceptible to caspofungin. Most (85-100%) isolates were susceptible to antifungal drugs, but 3.13 - 6.25% were resistant to voriconazole and fluconazole. In conclusion, our findings revealed that C. parapsilosis sensu stricto was the most common species among clinical isolates of the C. parapsilosis complex, and the most commonly used antifungal agents generally exhibited good in vitro activity against these strains.